2010
DOI: 10.1152/ajpheart.00784.2009
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Na+and Ca2+transporters in arterial smooth muscle from ouabain-induced hypertensive rats

Abstract: Prolonged ouabain administration (25 microg kg(-1) day(-1) for 5 wk) induces "ouabain hypertension" (OH) in rats, but the molecular mechanisms by which ouabain elevates blood pressure are unknown. Here, we compared Ca(2+) signaling in mesenteric artery smooth muscle cells (ASMCs) from normotensive (NT) and OH rats. Resting cytosolic free Ca(2+) concentration ([Ca(2+)](cyt); measured with fura-2) and phenylephrine-induced Ca(2+) transients were augmented in freshly dissociated OH ASMCs. Immunoblots revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
131
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(141 citation statements)
references
References 83 publications
10
131
0
Order By: Relevance
“…87 Another limitation is that the concept of intracellular Ca 2þ regulation by high affinity NaKAs has been partially based on other vascular beds than the cerebral circulation. 25,56 More research is thus needed to investigate these mechanisms in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…87 Another limitation is that the concept of intracellular Ca 2þ regulation by high affinity NaKAs has been partially based on other vascular beds than the cerebral circulation. 25,56 More research is thus needed to investigate these mechanisms in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…A likely possibility is that receptoroperated channels (ROCs), which are an important source of Ca 2ϩ during receptor activation (44), especially at high catecholamine concentrations (30), may be downregulated in NCX1 SMϪ/Ϫ arteries. In primary cultured arterial myocytes, a knockout of NCX1 markedly decreases the expression of transient receptor potential canonical 6 channel protein (a component of ROCs) and reduces ROC activity (33).…”
Section: Similarity Of Effects Of Genetic and Pharmacological Knockoumentioning
confidence: 99%
“…Moreover, the SM-specific overexpression of NCX elevates BP and induces salt-dependent hypertension, and SEA0400 lowers BP in several salt-dependent animal models (21). Indeed, NCX type-1 (NCX1) is upregulated in mesenteric arteries from rats with ouabain-induced hypertension (33) and pulmonary arteries from humans with primary pulmonary hypertension (49). Whether NCX is involved in maintaining normal BP, however, has not been resolved.…”
mentioning
confidence: 99%
“…These findings indicate that salt-sensitive hypertension is linked to Ca 2ϩ entry through NCX1 in arterial smooth muscle (14). Indeed, NCX1 protein is upregulated in arteries in several types of hypertension (23,31,36,39).…”
mentioning
confidence: 81%
“…Renovascular function plays a pivotal role in salt-dependent hypertension (9,34), and it has been reported that Na ϩ /Ca 2ϩ exchanger mechanisms are disrupted in saltsensitive hypertension (2,21,32). In contrast, other groups observed enhanced expression of NCX1 in arterial smooth muscle in several forms of hypertension (10,23,39). This might imply that NCX-mediated Ca 2ϩ transport is enhanced under these circumstances.…”
mentioning
confidence: 99%